Association between thrombophilia and the post‐thrombotic syndrome: a systematic review and meta‐analysis. (January 2014) - Rabinovich, A.; Cohen, J. M.; Prandoni, P.; Kahn, S. R.
Summary Background The postthrombotic syndrome (PTS) is a frequent chronic complication of deep vein thrombosis (DVT), occurring in 20–40% of patients. Identifying risk factors for PTS may be useful to provide patients with prognostic information and target prevention strategies. Objective To conduct a systematic review to assess whether, among patients with DVT, inherited and acquired thrombophilias are associated with a risk of PTS. Methods We searched the electronic databases PubMed, EMBASE, Scopus, and Web of Science for studies published from 1990 to 2013 that assessed any thrombophilia in adult DVT patients and its association with the development of PTS. We calculated odds ratios and 95% confidence intervals for PTS according to the presence of thrombophilia. Meta‐analysis was performed using the random‐effects model. Results Sixteen studies were included: 13 assessed factor V Leiden (FVL), 10 assessed prothrombin mutation, five assessed protein S and C deficiencies, three assessed antithrombin deficiency, four assessed elevated FVIII levels, and six assessed antiphospholipid antibodies. None of the meta‐analyses identified any thrombophilia to be predictive of PTS. Both FVL and prothrombin mutation appeared protective among studies including patients with both first and recurrent DVT and studies in which more than 50% of patients had an unprovoked DVT. Conclusions Our meta‐analysis did not demonstrate a significant association between any of the thrombophilias assessed and the risk of PTS in DVT patients. Other biomarkers in the pathophysiological pathway may be more predictive of PTS.